Highlighting the use of micro and nanoparticles based-drug delivery systems for the treatment of Helicobacter pylori infections. (4th July 2021) - de Souza, Maurício Palmeira Chaves; de Camargo, Bruna Almeida Furquim; Spósito, Larissa; Fortunato, Giovanna Capaldi; Carvalho, Gabriela Corrêa; Marena, Gabriel Davi; Meneguin, Andréia Bagliotti; Bauab, Taís Maria; Chorilli, Marlus
Abstract: Due to the high adaptability of Helicobacter pylori and the low targeting specificity of the drugs normally used in pharmacological therapy, the strains are becoming increasingly resistant to these drugs, making it difficult to eradicate the infection. Thus, the search for new therapeutic approaches has been considered urgent. The incorporation of drugs in advanced drug delivery systems, such as nano and microparticles, would allow the improvement of the retention time in the stomach and the prolongation of drug release rates at the target site. Because of this, the present review article aims to highlight the use of micro and nanoparticles as important technological tools for the treatment of H. pylori infections, focussing on the main nanotechnological systems, including nanostructured lipid carriers, liposomes, nanoemulsion, metallic nanoparticles, and polymeric nanoparticles, as well as microtechnological systems such as gastroretentive dosage forms, among them mucoadhesive, magnetic and floating systems were highlighted.